PENINGKATAN HASIL BELAJAR SISWA KELAS XI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA MATERI TURUNAN FUNGSI ALJABAR - Titaley, A M; Ayal, C S; Gaspersz, M (Jurusan Pend. MIPA FKIP Universitas Pattimura, 2023)
This research aims to find out whether with the think pair share type cooperative learning model, the learning outcomes of class XI students at SMA Negeri 1 Kairatu can be improved. The subjects in this research were 20 students in class XI of SMA Negeri 1 Kairatu. Tests are given at the end of the meeting of each cycle, while observations are given at each meeting. The observation results obtained pay attention to indicators of student learning activities during the action. The change that can be seen is that each pair was able to work better in cycle II than cycle I. Based on the final test results, there was an increase in student learning outcomes by 30%. In cycle I, the percentage of students who achieved the minimum completeness criteria was 50%, then in cycle II it increased to 80%. These results state that the think pair share type cooperative learning model can improve the learning outcomes of class XI students at SMA Negeri 1 Kairatu in derivative of algebraic function material.